MANDREL: Modular Reinforcement Learning Pipelines for Material Discovery - Fare, Clyde; Holt, George K.; Chiazor, Lamogha; Smyrnakis, Michail; Tracey, Robert; Hoang, Lan (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
AI-driven materials discovery is evolving rapidly with new approaches and pipelines for experimentation and design. However, the pipelines are often designed in isolation. We introduce a modular reinforcement learning framework for inter-operable experimentation and design of tailored, novel molecular species. The framework unifies reinforcement learning (RL) pipelines and allows the mixing and matching of choices for the underlying chemical action space, molecular representation, desired molecular properties, and RL algorithm. Our demo showcases the framework’s capabilities applied to benchmark problems like quantitative estimate of drug-likeness and PLogP, as well as the design of novel small molecule solvents for carbon capture.